Chapter 2. Test yourself - Santos, Jorge (Septentrio Educational, 2015)
This introductory chapter of CONΣERV IT deals with the following preparatory skills: - Am I aware of the basics of scientific writing required to write an informative report? - Do I remember the basics of mathematics? - How do I use statistics to plan and analyze my field or experimental data?